CAREGIVERS' QUALIFICATION OF DISCHARGED PATIENTS - Ana Paula Felix; Ana Maria Dyniewicz; Andreia Pereira Martins (Universidade Federal do Paraná, 2008)
A project was developed targeting caregivers of patients with neurological sequelae and aiming their homecare qualification on clinic and surgical neurology at a teaching hospital. Qualification was carried out by nurses, nutritionistsand physical therapists. Methodology was patient and caregiver's identification, team assessment, daily report, evaluationand case report. The article describes such steps, with 12 patients along 2004, analyzing follow up and pointing out waysfor implementation. Among the project potentialities, it can be pointed out: access to patients and records; families' andpatients' security at discharge; collaboration at the units; access to bibliography, supplies and equipment. Among theshortcomings, it can be mentioned: work overload; team's organization and caregivers' availability. The exercise ofprofessional autonomy was evidenced in the project although team harmony and working conditions are complex andefforts are demanded in order to organize, implement and assess educational actions.